Conceptualization of the concept of occupational burnout in the scientific literature - Galan, Lina; Zhuravlova, Olena; Kulchytska, Anna (Psychological Prospects Journal, 2024)
Purpose. The article reveals the concept of professional burnout in the scientific literature.Methods. To achieve the goal, the following methods of scientific and theoretical study of the problem were used in the study: analysis, synthesis, comparison, generalization, abstraction, systematization of scientific research on the issues of professional burnout.Results. According to the results, it was found that Professional activity occupies one of the key positions in human life, as it becomes not only a means of meeting material needs, but also an important factor for self-realization and self-expression of the individual. In the modern world, with its high dynamism and rapid changes in the socio-economic environment, employees are faced with growing competition in the labor market, continuous changes in the organizational environment and a large amount of work.The outlined trends create conditions for the emergence of professional burnout syndrome, which generates destructive consequences for both the individual and the organization as a whole, determining a decrease in labor productivity, loss of qualified personnel and deterioration of the working climate.Emotional exhaustion is the first reaction to excessive workload and professional stress, which manifests itself in a feeling of constant general fatigue, lack of energy, and a decrease in the level of enthusiasm. Loss of interest in professional tasks is accompanied by the emergence of beliefs about the lack of meaning in their implementation. Negative emotional states such as depression, irritability, depression, impulsivity are often combined with somatic manifestations, for example, sleep disorders, gastrointestinal disorders, headaches, etc.Conclusions. Burnout syndrome is a profound transformation of the personality, which is a consequence of experiencing chronic stress in the process of work and has a destructive effect on the emotional state of the employee, his relationships with the social environment and self-perception in the professional sphere. Burnout has negative consequences for both the individual employee and the organization. A person experiences the negative consequences of this condition in the form of deterioration of physical and mental health. Such disintegration of the personality “distorts” his further life and career prospects. In turn, employees with burnout syndrome do not properly perform their job duties, often make mistakes and make minimal efforts to achieve organizational goals, which leads to a number of negative consequences for the functioning of the institution in which such a specialist works.